Los modelos neoclásicos de desarrollo sostenible y la noción de "sostenibilidad débil" (2006)
This article provides an analysis of neoclassic models of sustainable development from which some gains and limitations in the taking of economic decisions can be identified; especially when dealing with the application of measures related to environmental economic policies.